2011
DOI: 10.1038/ijo.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the association of insulin and the insulin-like growth factor axis with colorectal neoplasia

Abstract: Objective: Accumulating evidence has implicated insulin and the insulin-like growth factor (IGF) axis in colorectal carcinogenesis. Of interest, adiposity is likely to impose a greater risk on men than on women, which indicates that the association of insulin and the IGF axis with colorectal neoplasia may differ by gender. However, epidemiological evidence for this possible gender difference is limited to date. Methods: We measured plasma concentrations of C-peptide, IGF-I and IGF-binding proteins (IGFBPs) 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
5
28
2
Order By: Relevance
“…Several genetic and epigenetic factors have been suggested to explain sex-specific differences in CRC risk [38]. Insulin and insulin-like growth factor axis may act differently by sex in CRC carcinogenesis [39]. Our findings suggest that adiposity may impose a different risk on CRC by sex, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 64%
“…Several genetic and epigenetic factors have been suggested to explain sex-specific differences in CRC risk [38]. Insulin and insulin-like growth factor axis may act differently by sex in CRC carcinogenesis [39]. Our findings suggest that adiposity may impose a different risk on CRC by sex, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 64%
“…Estrogen may exert a protective effect through the insulin/IGF axis by reducing serum IGF levels (21) and alter the bile acid pool, which is believed to play an important role in colon carcinogenesis (35). Additionally, Yamaji et al (36) identified that the insulin/insulin-like growth factor-1(IGF) axis acts differently by gender in colorectal carcinogenesis, at least in its early stage. Besides, several studies reported that the association between obesity and CRC risk among women would differ according to the levels of their estrogen status (premenopausal vs. postmenopausal) (15,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…For colorectal adenomas, however, the relationship with C-peptide levels is less certain. The majority of previous studies investigating the circulating C-peptide-colorectal adenoma relationship have been case-control studies, which have usually reported positive relationships [13][14][15]. These studies are vulnerable to reverse causality as serum samples were collected from cases after adenoma diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between insulin levels or C-peptide levels and colorectal adenoma has rarely Cancer Epidemiology xxx (2015) xxx-xxx been investigated prospectively. Case-control studies have usually reported positive associations between circulating levels of Cpeptide or insulin and colorectal adenomas risk [13][14][15], but the two previous prospective investigations have reported contrasting findings, with one reporting a positive relationship [16] and the other a null result [17].…”
Section: Introductionmentioning
confidence: 92%